Spanglerelmis, a new genus of Elmidae (Insecta: Coleoptera) from Brazil with new species and biological notes - Polizei, Thiago Tadeu Silva; Costa, Lucas de Souza Machado; Bispo, Pitágoras da Conceição [UNESP] (Museum National D'Histoire Naturelle, 2022)
In this study, the new genus Spanglerelmis Polizei & Bispo is described; Microcylloepus ochus Hinton, 1940 is synonymized with Microcylloepus femoralis Hinton, 1940, and transferred to the new genus; and two new species, S. xiririca gen. et sp. nov. and S. timburi gen. et sp. nov. are described. The new genus can be characterized by the combination of the following characters: 1) pronotum without transverse, longitudinal or oblique impressions, sulci or gibbosities on disc; 2) elytra with a carina on interval III and two sublateral carinae on intervals V and VI; 3) mesoventrite with sides strongly raised; and 4) femora with an oblique belt of tomentum dorsally and a transverse belt ventrally. The specimens of the two new species were collected mainly in riffles of unimpacted streams in the Atlantic Forest in São Paulo State, Brazil. Scanning electron microscope images, an identification key for the genus and habitat notes are also presented.
Keywords: Aquatic beetles; Neotropical; new genus; new species; riffle beetles; South America